Theoretical analysis and experimental investigation of material compatibility between refrigerants and polymers. (15th November 2018) - Eyerer, Sebastian; Eyerer, Peter; Eicheldinger, Markus; Tübke, Beatrice; Wieland, Christoph; Spliethoff, Hartmut
Abstract: A new generation of refrigerants, the hydrofluoroolefines, has been introduced within the last years. These fluids have a significantly smaller Global Warming Potential compared to the state-of-the-art fluids, which are within the class of hydrofluorocarbons. The hydrofluoroolefines are unsaturated molecules consisting of double-bonded carbon atoms. Especially, compared to hydrofluorocarbons, which are saturated molecules, the interaction with polymers might differ. Therefore, this study investigates the compatibility between polymers and refrigerants, which are commonly used as working fluids in Organic Rankine Cycles or refrigeration units. The compatibility is evaluated due to a theoretical analysis of the relevant mechanisms of the fluid-polymer interaction and an experimental study. The investigated refrigerants are two state-of-the-art fluids, namely R245fa and R134a, as well as three next-generation refrigerants R1233zd-E, R1234yf and R1234ze-E. In addition, two blends, namely R450a and R513a, as well as a lubricant polyolester are investigated. The polymers comprise six elastomers and two thermoplastics, more specifically, two different compositions of ethylene-propylene-diene rubber, two compositions of fluororubber, chlorobutadiene rubber, nitrile-butadiene rubber, polytetrafluoroethylene and polypropylene. The material compatibility is evaluated by changes in volume, weight, Shore hardness as well as in small load hardness. Summing up, 64 different fluid-polymer combinations are tested at two different temperature levels. Highlights: Material compatibility analysis between refrigerants and polymers. Brought experimental program with 64 different fluid-polymer combinations. In depth theoretical analysis of the mechanisms for fluid-polymer interaction. Novel evaluation approach incorporating theoretical and experimental investigation.